FAKTOR-FAKTOR TERJADINYA STUNTING PADA BALITA USIA 3 – 5 TAHUN DI KECAMATAN CIKAKAK KABUPATEN SUKABUMI - Erina Feliana; Alib Birwin; Yoli Farradika (Politeknik Kesehatan Kementerian Kesehatan Banten, 2022)
Stunting is a chronic nutritional problem in toddlers, characterized by a shorter height than their age. According to data from the Sukabumi District Health Office, the Prevalence of stunting at the Cikakak Public Health Center is the highest compared to other health centres. This study aimed to determine the factors associated with stunting in toddlers aged 3-5 years in Cikakak District, Sukabumi Regency, in 2021. This study used a cross-sectional design. The subjects studied were toddlers aged 3-5 years in the Cikakak district. The samples were 144 respondents using the proportionate stratified random sampling technique. The data used in this study are primary data using measurement and questionnaire interviews. The data analysis used in this study was univariate and bivariate analysis using the Chi-Square test. The results of this study indicate that there is a relationship between under-five factors such as low birth weight (0.036), history of infectious disease (<0.001) and parental factors such as maternal age (0.004), mother's education (0.015), income (0.001), exclusive breastfeeding (0.023), and knowledge maternal nutrition (<0.001). In response to this, it is necessary to educate mothers about the importance of preventing stunting for toddlers so that in the future, the stunting rate in Cikakak District can decrease.